'Instructing readers' minds in heavenly matters': Carolingian History Writing and Christian Education. (3rd June 2019) - Evans, Robert A. H.
Abstract : This article explores the ways in which histories were used in the moral and doctrinal education of Christian elites in the West from the late Roman to the Carolingian periods. In the sixth century, Cassiodorus wrote that histories, whether Christian or not, were useful for 'instructing the minds of readers in heavenly matters'. How far was this characteristic of the period? Traditionally, scholars have emphasized either the apologetic purpose or the moral of specific histories, such as Orosius's Historiae or Bede's Historia Ecclesiastica . Few modern scholars, however, have examined the long-term development of history writing as a vehicle for Christian education during the transformation of the Roman world. Those who have done, such as Karl-Ferdinand Werner and Hans-Werner Goetz, have emphasized continuity rather than change. The article sketches some of the changes and continuities across the period. In particular, it demonstrates that there was a shift from the apologetic concerns of the fifth-century historians, writing to educate Christians from pagan backgrounds, to the doctrinal (as much as moral) concerns of Frankish historians, emerging from the Carolingian Renaissance.